Preliminary Study of Reducing Sugar Production from Coconut Husk by Enzymatic Hydrolysis Using Chitosan Immobilized Crude and Commercial Cellulase - Afan Hamzah; Muhammad Nurul Hakim; Baiq Firyal Salsabilla Safitri; Nurul Maziyah; Laila Nur Rahmah; Hanny F Sangian; Soeprijanto Soeprijanto; Arief Widjaja (IPTEK The Journal for Technology and Science, 2020)
The objective of this research was to study the production of sugar from coconut husk using immobilized crude and commercial cellulose, including temperature and mixing speed during immobilization. The enzyme from Aspergillus Niger was immobilized on chitosan alone and cross-linked with Glutaric Dialdehyde (GDA). Coconut husk waste was grinded and chemically pretreated using NaOH 1% (w/v). Fourier Transform Infrared Spectroscopy (FT-IR) measurement revealed that enzyme was covalently bonded to the support. Cellulose immobilized on chitosan cross-linked with GDA produced more sugar than immobilized on chitosan alone. Both the crude and commercial enzyme had their yield decreased after immobilization. Despite its less enzyme coupled on micro-sized chitosan, reducing sugar yielded by an immobilized enzyme on micro-sized chitosan had a competitive result with macro-sized chitosan. This may due to decreasing mass transfer resistance when using a smaller size of chitosan. Several important factors such as temperature, mixing speed, and purity of enzyme responsible for the performance of sugar produced from insoluble cellulose using cellulose immobilized on insoluble support was thoroughly discussed.